Pemanfaatan Sistem GPS (Global Positioning System) Pada Announcer Otomatis Untuk Pemberhentian Kereta Api dan Monitoring Kecepatan - Muhammad Abi Rahmatputra (Politeknik Negeri Malang, 2016)
Trains are one of the most popular public transportations for consumers in Indonesia when they travel. For the service of providing information on the announcement of the next station stop, it has begun to be implemented in almost all train journeys, but in terms of delivery it is still manually using loudspeakers with sound system devices. This system uses a tablet with Android OS as the main control. The communication system utilizes the GPS system when the tracking process with additional data access is more accurate. For the input data, namely the voice recording data of the announcer for each station to be visited and the parameter data of the coordinate points before entering the stopping station. The system created will track the train route and issue an announcer sound on the sound system and the speed feature will be displayed in real time on this application. From the test results 10 times the implementation on the announcer train has sounded automatically according to the plan range area of ??± 2 km before entering the station. For data records, the highest delay time for data reception is 3 seconds. In the average difference from the calculation of the sample data record distance with the Euclidean theorem is 19 meters while the Haversine theorem is 22 meters.